A study of the psychological experience of patients with thromboembolism during pregnancy and after childbirth (孕产期血栓栓塞症患者真实心理体验的研究) - HU Jiali (胡嘉丽); HUANG Xuefang (黄学芳); XU Xiaoyun (徐晓耘); MENG Ya (孟雅) (中西医结合护理)
Objective To understand the psychological experience of patients with thromboembolism during pregnancy and after childbirth. Methods A total of 100 patients with thromboembolism during pregnancy or after delivery were selected as the research subjects. All patients completed the Symptom Check List-90 (SCL-90) on the first day of admission and before discharge. Ten patients were randomly selected for a semi-structured qualitative interview to understand their psychological experience of and reaction to thromboembolism. Results The factor scores of somatization, anxiety, depression, paranoid ideation and interpersonal sensibility decreased significantly after hospitalization management compared with those before hospitalization management(P＜0. 01). Qualitative findings were distilled into two major themes: low disease knowledge and awareness among patients with thromboembolism during pregnancy and after childbirth; increased psychological burden as excessive fear of disease and concerns about fetus and newborns. Conclusion Efforts such as risk assessment, risk factors analysis and health education should be made to enhance the non-hospitalized self-prevention and management in women during pregnancy and after childbirth. Early implementation of targeted interventions should also be mentioned to strengthen psychological care for pregnant women, in order to reduce the blindness and passivity of behavior. (目的 了解孕产期血栓栓塞症患者的真实心理体验。方法 选取医院收治的孕产期血栓栓塞症患者100例为研究对象, 所有患者在入院第一天及出院前填写症状自评量表(SCL-90), 了解住院管理前后患者的心理状态。采用质性研究方法, 选取10名孕产妇进行半结构式访谈, 了解患血栓栓塞症后的真实心理体验。结果 住院管理后, SCL-90量表中躯体化、焦虑、抑郁、偏执、人际关系敏感性维度评分均较住院管理前降低, 差异有统计学的意义(P＜0. 01)。质性访谈结果显示, 孕产期血栓栓塞症患者对疾病知识缺乏认知; 患者因对疾病的过度恐惧及对胎儿/婴儿产生影响的担忧而导致心理负担增加。结论 应做好孕产期血栓栓塞症风险筛查, 在探讨危险因素的同时, 加大科普宣传和健康宣教力度, 帮助孕产妇提升自我预防及管理能力。入院后提前实施针对性干预措施, 加强患者心理护理, 能够减少孕产妇行为的盲目性和被动性。)